2021
DOI: 10.1097/mop.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in children and young adults with cancer

Abstract: Purpose of reviewThe issue of fertility preservation has become increasingly relevant as survival rates of children with cancer exceeds 80% at 5 years. Fertility preservation options are being utilized alongside less gonadotoxic therapeutic regimens in the treatment of these patients. The purpose of this review is to summarize the recent advances in fertility preservation in the pediatric, adolescent, and young adult population. Recent findingsEducation research involves both patient and provider; to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Other challenges connected with OTC and OTT include previous chemotherapy and the risks of reintroducing malignant cells together with frozen-thawed ovarian tis-sue [79,[82][83][84]. While it was suggested that OTC should be performed before chemotherapy starts [21,79], a study performed by Dolmans et al found that chemotherapy before OTC did not alter the results of OTT, and the authors suggested that it should no longer be considered a contraindication.…”
Section: Fertility Preservation Methods: To Whom When and How They Sh...mentioning
confidence: 99%
“…Other challenges connected with OTC and OTT include previous chemotherapy and the risks of reintroducing malignant cells together with frozen-thawed ovarian tis-sue [79,[82][83][84]. While it was suggested that OTC should be performed before chemotherapy starts [21,79], a study performed by Dolmans et al found that chemotherapy before OTC did not alter the results of OTT, and the authors suggested that it should no longer be considered a contraindication.…”
Section: Fertility Preservation Methods: To Whom When and How They Sh...mentioning
confidence: 99%
“…[57][58][59][60] The Pan-CareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group provide a review for anyone having this discussion with patients and consensus guidelines on fertility preservation. 52 We recommend consideration of early referral to reproductive specialists with communication regarding the type of cancer and stage, anticipated treatment, including CED/ alkylating dose, and the recommended timeline for the patient to initiate treatment. Automating this step may be accomplished by implementing an electronic health record advisory that flags the charts of patients with newly diagnosed cancer.…”
Section: Recommendations To Address Gapsmentioning
confidence: 99%
“…Certain malignancies, such as central nervous system and hematologic cancers, carry a higher risk of infertility than certain solid tumors. 52 In general, alkylating agents and heavy metals are likely to affect spermatogenesis. 53 Witt and Bishop 54 demonstrated the mutagenic profile of 21 anticancer drugs in murine models and found that certain drugs are more likely to cause cell damage than others.…”
Section: Current Gaps In Knowledge Of the Utilization Of Post-treatme...mentioning
confidence: 99%
See 2 more Smart Citations